Autologous Gene and Cell Therapy Provides Safe and Long-Term Curative Therapy in A Large Pig Model of Hereditary Tyrosinemia Type 1. Issue 1 (January 2019) - Hickey, Raymond D.; Nicolas, Clara T.; Allen, Kari; Mao, Shennen; Elgilani, Faysal; Glorioso, Jaime; Amiot, Bruce; VanLith, Caitlin; Guthman, Rebekah; Du, Zeji; Chen, Harvey; Harding, Cary O.; et al.
Orthotopic liver transplantation remains the only curative therapy for inborn errors of metabolism. Given the tremendous success for primary immunodeficiencies using ex-vivo gene therapy with lentiviral vectors, there is great interest in developing similar curative therapies for metabolic liver diseases. We have previously generated a pig model of hereditary tyrosinemia type 1 (HT1), an autosomal recessive disorder caused by deficiency of fumarylacetoacetate hydrolase (FAH). Using this model, we have demonstrated curative ex-vivo gene and cell therapy using a lentiviral vector to express FAH in autologous hepatocytes. To further evaluate the long-term clinical outcomes of this therapeutic approach, we continued to monitor one of these pigs over the course of three years. The animal continued to thrive off the protective drug NTBC, gaining weight appropriately, and maintaining sexual fecundity for the course of his life. The animal was euthanized 31 months after transplantation to perform a thorough biochemical and histological analysis. Biochemically, liver enzymes and alpha-fetoprotein levels remained normal and abhorrent metabolites specific to HT1 remained corrected. Liver histology showed no evidence of tumorigenicity and Masson's trichrome staining revealed minimal fibrosis and no evidence of cirrhosis. FAH-immunohistochemistry revealed complete repopulation of the liver by transplanted FAH-positive cells. A complete histopathological report on other organs, including kidney, revealed no abnormalities. This study is the first to demonstrate long-term safety and efficacy of hepatocyte-directed gene therapy in a large animal model. We conclude that hepatocyte-directed ex-vivo gene therapy is a rational choice for further exploration as an alternative therapeutic approach to whole organ transplantation for metabolic liver disease, including HT1.